Informed Consent as an Instrument of Legal Protection for Dentists - Arief Budiono; Ichsan Khalid Sapnosa; Abdullah al Mamun (Jurnal Hukum Volkgeist, 2023)
Informed Consent is patient consent based on an explanation by a doctor at the hospital and is used in law and medicine to protect the public as a patient who receives health services based on information provided by the hospital through a dentist. Informed consent is mandated by law to protect patients and medical professionals, especially dentists. It offers patients the comfort they need to make their own decisions. For dentists, it aims to provide legal protection against the risk of imposition associated with deficiencies in medical action. This was normative research, which examines the law along with literature studies. It aimed to find out how to apply informed consent and to find out the legal protection related to informed consent for medical staff. In the Ministry of Health's Decision No. 290 of 2008 concerning the Legalization of Medical Actions, a doctor's complete explanation for the patient must include the diagnosis and implementation of the medical action, alternative actions and risks, possible complications, prognosis for the procedure, and financing. Patients can make an informed decision after receiving a thorough explanation as they have the freedom to refuse the recommended treatment and seek a second opinion. Legal protection for medical staff in Article 50 of Law No. 29/2004 Medical Practice and Article 57 of Law No.36/2014 regarding Health Workers.